CRISPR-Cas-based techniques for pathogen detection: Retrospect, recent advances, and future perspectives - Huang, Tao; Zhang, Rui; Li, Jinming (Journal of advanced research, 2023)
[Display omitted] •Early pathogen detection is critical for disease treatment, prevention, and control.•Traditional pathogen detection techniques based on polymerase chain reaction are limited by the high cost of reagents and instruments, as well as the harsh technical operation.•The development of novel pathogen diagnosis methods that are quick, sensitive, focused, portable, and affordable is difficult but vital.•CRISPR-Cas-based biosensing technology has the potential to be an ideal pathogen diagnostic tool.•Technology's transition from the laboratory to the clinical diagnosis depends on standardization. Early detection of pathogen-associated diseases are critical for effective treatment. Rapid, specific, sensitive, and cost-effective diagnostic technologies continue to be challenging to develop. The current gold standard for pathogen detection, polymerase chain reaction technology, has limitations such as long operational cycles, high cost, and high technician and instrumentation requirements. This review examines and highlights the technical advancements of CRISPR-Cas in pathogen detection and provides an outlook for future development, multi-application scenarios, and clinical translation. Approaches enabling clinical detection of pathogen nucleic acids that are highly sensitive, specific, cheap, and portable are necessary. CRISPR-Cas9 specificity in targeting nucleic acids and “collateral cleavage” activity of CRISPR-Cas12/Cas13/Cas14 show significant promise in nucleic acid detection technology. These methods have a high specificity, versatility, and rapid detection cycle. In this paper, CRISPR-Cas-based detection methods are discussed in depth. Although CRISPR-Cas-mediated pathogen diagnostic solutions face challenges, their powerful capabilities will pave the way for ideal diagnostic tools.